2018
DOI: 10.1029/2018jc014265
|View full text |Cite
|
Sign up to set email alerts
|

Surface Salinity Balance in the Tropical Pacific Off Mexico

Abstract: A simplified analytical model was used to solve the salinity balance equation and study the relative contributions of freshwater flux and salt advection to the salinity tendency between the Gulf of Tehuantepec and Cabo Corrientes (14–22°N). The model used climatological mixed‐layer salinity, satellite‐derived geostrophic velocity and evaporation minus precipitation data in a four‐domain scheme. The mean circulation derived from the model largely coincides with previous reports and suggests that, in the steady … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…1) formed part of a system of fronts resulting from the transport of waters of different origins by the tropical branch of the California Current and by the Mexican Coastal Current. The former transports subpolar water to tropical latitudes (Godínez et al, 2010;Portela et al, 2016), while the latter transports tropical waters poleward (Willett et al, 2006;Portela et al, 2018). These current systems converge in and around the study area, where they mix and interact with Gulf of California waters intensifying the mesoscale processes in the region (Fiedler and Talley, 2006;Portela et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1) formed part of a system of fronts resulting from the transport of waters of different origins by the tropical branch of the California Current and by the Mexican Coastal Current. The former transports subpolar water to tropical latitudes (Godínez et al, 2010;Portela et al, 2016), while the latter transports tropical waters poleward (Willett et al, 2006;Portela et al, 2018). These current systems converge in and around the study area, where they mix and interact with Gulf of California waters intensifying the mesoscale processes in the region (Fiedler and Talley, 2006;Portela et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…The former transports subpolar water to tropical latitudes (Godínez et al, 2010;Portela et al, 2016), while the latter transports tropical waters poleward (Willett et al, 2006;Portela et al, 2018). These current systems converge in and around the study area, where they mix and interact with Gulf of California waters intensifying the mesoscale processes in the region (Fiedler and Talley, 2006;Portela et al, 2018). Biologically, this water mass convergence region has been little studied to date, but some authors like Etnoyer et al (2006) have suggested that the contribution of the mesoscale activity to primary productivity could be high, given the high frequency and abundance of top predators in the region.…”
Section: Discussionmentioning
confidence: 99%
“…The paralarvae remain in planktonic phase up to ~ 10 mm ML, when the proboscis splits to form the tentacles (Camarillo-Coop et al , 2013;Zepeda-Benitez et al, 20 14). The plank:tonic life stages, as in all the meroplank:tonic organisms, are the most sensitive to environmental changes and are exposed to higher mortality rates than later ontogenetic stages (Camarillo-Coop et al , 2013;et al , 2010a;Gomez-Valdivia et al , 2015 ;Portela et al , 2018;Sanchez-Velasco et al , 2017. A fourth water mass, with wide thermal range (12 °C < temperature < 32 °C) and high salinity(> 35.1 g kg-1 ) and originating in the Gulf of California, contributes to the interaction and mixing between these three water masses near the entrance of the Gulf.…”
Section: Introductionmentioning
confidence: 99%
“…1) (Durazo, 2015;Godinez et al , 201 0a;Lavin and Marinone, 2003). During summer and autumn, wind from the southeast drives predominantly poleward flow (Gomez-Valdivia et al , 2015 ;Lavin et al , 2006;Portela et al, 2018). The arrival of tropical surface water in the southern Gulf of California typically deepens the thermocline (Godinez et al , 201 0a;Portela et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the transition zone the surface temperatures oscillate between 18 and 30 °C, and surface salinity varies from 35.1 to 34 g/kg during spring and autumn, respectively (Fiedler & Talley, ). In spring and winter, the intrusion of the tropical branch of the California Current (Kurczyn et al, ) ventilates the hypoxic subsurface waters, while during summer and autumn the influence of the Mexican Coastal Current (Lavín et al, ; Portela et al, ) transport hypoxic and suboxic waters from the tropical domain to the transition zone, rising the hypoxic waters in the area (Márquez‐Artavia et al, ).…”
Section: Introductionmentioning
confidence: 99%